The Role of Artificial Intelligence in Learning Foreign Languages - Bakhromkhodja, Makhamadkhodjaev (Innovative Technologica: Methodical Research Journal, 2024)
The article explores the role of artificial intelligence (AI) in the process of learning foreign languages, analyzing both positive and negative aspects of this phenomenon. Based on current research and practical examples, the article discusses the impact of various I-technologies, such as machine learning and natural language algorithms, on the effectiveness and efficiency of language learning. The analysis examines the advantages of AI, such as accessibility, individualization of learning and the possibility of real-time feedback, as well as disadvantages, including limitations in understanding the context, lack of flexibility and dependence on technical means.